2005
DOI: 10.1021/cm0518980
|View full text |Cite
|
Sign up to set email alerts
|

Chemical, Thermal, and Ultrasonic Stability of Hybrid Nanoparticles and Nanoparticle Multilayer Films

Abstract: Gold nanoparticles stabilized by thiolates derived from normal and ω-functionalized alkane-and arenethiols (HS(CH 2 ) n CH 3 , HS(CH 2 ) 10 COOH, HS(CH 2 ) 11 OH, HSC 6 H 4 NH 2 , HSCH 2 CH 2 C 6 H 5 , and HSCH 2 C 6 H 4 C(CH 3 ) 3 ) were synthesized. Differences in their chemical and ultrasonic stabilities were studied using UV-vis spectroscopy. The results showed that these stabilities of monolayer-protected nanoparticles were greatly influenced by the structure and functionality of the monolayer surrounding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
57
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 37 publications
4
57
0
Order By: Relevance
“…The COOH-functionalized gold nanoparticles (MUA-NPs: average molecular formula of Au314L91) used for the film preparation were synthesized by the following methods. [33][34][35] Hexanethiolateprotected gold nanoparticles were first synthesized using a convenient two-phase synthesis known as the Schiffrin reaction. Briefly, AuCl4…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The COOH-functionalized gold nanoparticles (MUA-NPs: average molecular formula of Au314L91) used for the film preparation were synthesized by the following methods. [33][34][35] Hexanethiolateprotected gold nanoparticles were first synthesized using a convenient two-phase synthesis known as the Schiffrin reaction. Briefly, AuCl4…”
Section: Methodsmentioning
confidence: 99%
“…The incorporation of COOH-functional groups to the monolayer involved a modification of the hexanethiolate-protected gold nanoparticles by ligand-replacement. 34,35 In the exchange reaction, the incoming 11-mercaptoundecanoic acid (MUA) ligands replaced the hexanethiolate ligands on nanoparticles in THF by an associative reaction. The relative concentration of incoming ligands was carefully controlled for the synthesis of nanoparticles to have ~ 20% of COOH functional groups in the monolayers.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of these studies have been on monolayer protected clusters (MPCs), which are typically nanoparticles with diameters larger than 2 nm. Stability of nanoparticles depends on the chemical constitution and the shape of the core as well as the structure and the functionality of the ligands surrounding them [1]. It is reported that gold nanoparticles stabilized by monolayers of arenethiols have less thermodynamic stability than those stabilized by alkanethiols [2].…”
Section: Introductionmentioning
confidence: 99%